STUDY TENTANG PERILAKU PEMILIHAN KOSMETIKA DEKORATIF UNTUK MENINGKATKAN KEPERCAYAAN DIRI PADA MAHASISWI TATA RIAS DAN KECANTIKAN FPP UNP - Kartika Dewi; Hayatunnufus Hayatunnufus (Universitas Negeri Padang, 2021)
The idevelopment iof ithe icosmetics iindustry iat ithis itime iis ivery ihigh iand iits irole iis ivery iimportant iin ithe iworld iof ibeauty. i iDecorative icosmetics iare iindispenseble ifor iapplying imakeup iand icovering ithe ishorcomings ithat iexist iin ithe ifacial iskin iso ias ito iproduce ia imore iattractive iappearance iand ican ihave ia igood ipsychological ieffects ion ioneself. iThis istudy iaims ito i1) idescribe ithe iselection iof idecorative icosmetics iin iCoed iand iBeauty istudents i2) idescribe ithe iuse iof idecorative icosmetics ito iincrease iconfidence iin iCoed iand iBeauty istudents. iThis itype iof iresearch iis iqualitative iresearch iusing idescriptive imethods. iThe isource iof idata ior iinformants iin ithis istudy iis ia iStudent iof iMakeup iand iBeauty iof iPadang iState iUniversity. iData icollection itechniques iare icarried iout iby iconducting iobservations, iinterviews iand iresearch idocumentation. iTechniques ifor ianalyzing idata iinclude idata icollection, idata ireduction, idata ipresentation iand iconclusion idrawing. iThe iresults ishowed ithat iThe iStudent iof iMakeup iand iBeauty iof iPadang iState iUniversity ichose idecorative icosmetics ifor idaily ineeds. iIn iaccordance iwith ithe idevelopment iof iincreasingly isophisticated itechnology, iin igeneral irespondents iget iinformation iabout idecorative icosmetics ithrough irecommendations iby ifriends iand ionline imedia, isuch ias ifacebook, iyoutube, iand iinstagram. iThe iuse iof idecorative icosmetics iaims ito ilook ibeautiful, ias iwell ias ito icover ithe ishortcomings ithat iexist ion icertain iparts iof ithe iface. iHowever, imore iimportantly ithe irole iof idecorative icosmetics ican iincrease imore iconfidence iwhen iusing ithem. iBased ion ithe iresults iof ithe istudy, iit iis irecommended ithat iit ican ibe iused ias ia imaterial ito iadd iinsight iand iinformation iabout ithe iselection iand iuse iof idecorative icosmetics ifor iconfidence. iAnd ito irespondents iin iorder ito iincrease iconfidence iby iaccepting ithemselves imore ias ithey iare